2018
DOI: 10.1016/j.dcn.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for developmental longitudinal fMRI research

Abstract: There has been a large spike in longitudinal fMRI studies in recent years, and so it is essential that researchers carefully assess the limitations and challenges afforded by longitudinal designs. In this article, we provide an overview of important considerations for longitudinal fMRI research in developmental samples, including task design, sampling strategies, and group-level analyses. We first discuss considerations for task designs, weighing the pros and cons of many commonly used tasks, as well as outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 73 publications
(94 reference statements)
1
71
0
Order By: Relevance
“…For age, we explored both linear and nonlinear, quadratic models as previous studies have demonstrated both linear and nonlinear developmental trajectories in the brain [Telzer et al, 2018]. Figure 2 shows the inverted curvilinear relationship between age and percent signal change in four of the six insular subdivisions.…”
Section: Cardiac Interoceptive Accuracymentioning
confidence: 99%
“…For age, we explored both linear and nonlinear, quadratic models as previous studies have demonstrated both linear and nonlinear developmental trajectories in the brain [Telzer et al, 2018]. Figure 2 shows the inverted curvilinear relationship between age and percent signal change in four of the six insular subdivisions.…”
Section: Cardiac Interoceptive Accuracymentioning
confidence: 99%
“…It is particularly relevant to consider these transformations not only in relation to neural structural or localized activation changes, but also in relation to functional connectivity changes in the adolescent brain (Casey, ; Crone & Dahl, ; Stevens, ). Relative to studies examining structural (Tamnes et al, ) and functional (Telzer et al, ) brain development, very few studies have examined longitudinal functional connectivity changes. The goal of this study was therefore to analyze within and between subcortical–cortical connectivity in participants ages 8–29 years, using a three‐wave longitudinal design covering 5 years for each individual.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we charted adolescent changes in structural connectome organization, based on an accelerated longitudinal neuroimaging study (n = 208) 20,60 . Compared to cross-sectional designs, longitudinal studies track within-subject change, separating developmental effects from between-subject variability [61][62][63][64][65] . Leveraging connectome-wide manifold learning techniques 42 , we first estimated longitudinal changes in structural connectome manifolds across age in a compact and lower dimensional analytical space.…”
Section: Introductionmentioning
confidence: 99%